2013
DOI: 10.1021/jf4016043
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Equilibria of Ethanol on Cork

Abstract: We report here for the first time a thermodynamic study of gaseous ethanol sorption on raw cork powder and plate. Our study aims at a better understanding of the reactivity of this material when used as a stopper under enological conditions, thus in close contact with a hydroethanolic solution, wine. Sorption−desorption isotherms were accurately measured by thermogravimetry at 298 K in a large range of relative pressures. Sorption enthalpies were determined by calorimetry as a function of loading. Sorption−des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In any case, ethanol absorption appears to be responsible for a weakening of the intercellular cohesion in poplar wood cell walls. Vapour sorption measurements have already shown that ethanol might preferentially react with lignin rather than cellulose (Lequin et al 2013). Barrera-García et al (2008) showed a different behaviour of wood components towards sorption of phenolics from hydro-alcoholic solutions.…”
Section: Pure Solventsmentioning
confidence: 97%
“…In any case, ethanol absorption appears to be responsible for a weakening of the intercellular cohesion in poplar wood cell walls. Vapour sorption measurements have already shown that ethanol might preferentially react with lignin rather than cellulose (Lequin et al 2013). Barrera-García et al (2008) showed a different behaviour of wood components towards sorption of phenolics from hydro-alcoholic solutions.…”
Section: Pure Solventsmentioning
confidence: 97%
“…[8,25] Vapor sorption measurements have already shown that ethanol might be preferentially absorbed by lignin rather than cellulose. [26] The middle lamella, which is mainly composed of lignin and other phenolic compounds, might then preferentially interact with ethanol, being altered or even partially dissolved. This could explain the disbonding between primary wall and middle lamella.…”
Section: Optical Microscopy Of Water-ethanol Sodden Poplar Veneermentioning
confidence: 99%
“…For instance, Chandra and Koros used this balance to study the sorption of methanol vapor on poly(ethylene terephthalate) (PET). Similarly, Lequin et al used it to study the sorption of water vapor, sulfur dioxide and ethanol on cork. One needs to use test compounds with high enough volatility (minimum about 100 Pa).…”
Section: Experimental Techniques Used For Mass Transfer Studiesmentioning
confidence: 99%